Dosing time‐dependent effect of raloxifene on plasma plasminogen activator inhibitor‐1 concentrations in post‐menopausal women with osteoporosis1. (26th February 2013) - Ando, Hitoshi; Otoda, Toshiki; Ookami, Hitoshi; Nagai, Yukihiro; Inano, Akihiro; Takamura, Toshinari; Ushijima, Kentarou; Hosohata, Keiko; Matsushita, Eiki; Saito, Tetsuo; Kaneko, Shuichi; Fujimura, Akio
Summary Raloxifene, a selective oestrogen receptor modulator commonly used for the treatment of post‐menopausal osteoporosis, affects the coagulation and fibrinolytic systems and consequently increases the risk of venous thromboembolism. Because both the coagulation and fibrinolytic systems exhibit circadian rhythms, the aim of the present study was to investigate the effects of dosing time of raloxifene on markers of coagulation and fibrinolysis, as well as on markers of bone metabolism. Thirty‐nine post‐menopausal patients with osteoporosis were randomly allocated to two groups: one received 60 mg raloxifene once daily in the morning, whereas the other received 60 mg raloxifene once daily in the evening, for 12 months. In both groups, the activity of coagulation Factors IX and XII was increased significantly after 12 months treatment compared with baseline. The activity of coagulation Factors II and V and levels of markers of bone metabolism (i.e. bone alkaline phosphatase and tartrate‐resistant acid phosphatase 5b) decreased in both groups. The changes in these markers did not differ between the two groups. In contrast, the plasma concentration of plasminogen activator inhibitor (PAI)‐1 increased in the group receiving the morning dose (mean change 40.9%; 95% confidence interval (CI) 9.4, 72.5), but not in the groups receiving the evening dose (mean change −0.3%; 95% CI −31.5, 30.9); these percentage changes differed significantly (P < 0.05). Because an elevated concentration of PAI‐1 is known to be associated with the risk of venous thromboembolism, the findings of the present study suggest that the dosing time of raloxifene influences its safety. Further larger‐scale studies are needed to determine the clinical usefulness of chronotherapy with raloxifene.